Crescimento inicial de Enterolobium contortisiliquum (Vell.) Morong. em diferentes substratos e lâminas de irrigação - Fauerharmel, Mariana (2014)
The purpose of this work was to evaluate the development of Enterolobium contortisiliquum (Vell.) Morong seedlings produced with different substrates combined with irrigation water blade. The study was developed in the Tree Nursery of the Department of Forest Sciences at the Federal University of Santa Maria (UFSM-Universidade Federal de Santa Maria). The seeds used were collected from donor trees in the region of Santa Maria (RS). The substrates used were peat-based commercial (CS) and the mixture of the latter with carbonized rice husks (CRH), forming the following treatments: S1 (100% CS), S2 (80% CS + 20% CRH), S3 (60% CS + 40% CRH) and S4 (40% CS + 60% CRH) and the gross blades of daily irrigation water - GB-Gross Blades were 4, 8, 12, 16 and 20 mm.day-1. The design used was randomized blocks (four blocks) in a factorial scheme. The parameters height (H), stem diameter (SD) and H/SD ratio were obtained in a factorial scheme 4x5x4. For the aerial dry mass (ADM), root dry mass (RDM), total dry mass (TDM), ADM/RDM ratio and Dickson Quality Index (DQI), the factorial 4x5 was used respectively for the factors CS and irrigation blade, these parameters were obtained 150 days after sowing. One hundred and twenty days after sowing, the physiological parameters, chlorophyll a, chlorophyll b, total chlorophyll and carotenoids were evaluated and correlated with the morphological ones (H, SD and H/SD), also seen at 120 days. In this analysis we used 4x3 factorial, represented by four substrates and three blades gross daily irrigation (4, 12 and 20 mm.dia-1). The results indicated that the substrate based on peat mixed with 20% carbonized rice husk, when combined with gross irrigation blade of 8 mm.day-1 provides the appropriate seedlings Enterolobium contortisiliquum growth with greater economy of water and substrate. The correlation of morphological and physiological parameters observed in seedlings is low, so H, SD and H/SD may not be used for reference on the contents of chlorophyll. At 120 days after sowing, the height was greater in the 4 and 12 mm.day-1, possibly because 8 mm.day-1 was not used for analysis, while the diameter proved superior at S1 and S2, confirming the response at 150 days. As to the chlorophyll and carotenoid contents, they were larger when the seedlings received smaller amounts of water daily, indicating that the greater water blade compromised the seedling development and 20% of rice husk mixed with peat.